Comparisons of MRI images, and auditory-related and vocal-related protein expressions in the brain of echolocation bats and rodents. Issue 12 (17th August 2016) - Hsiao, Chun-Jen; Hsu, Chih-Hsiang; Lin, Ching-Lung; Wu, Chung-Hsin; Jen, Philip Hung-Sun
Abstract : Although echolocating bats and other mammals share the basic design of laryngeal apparatus for sound production and auditory system for sound reception, they have a specialized laryngeal mechanism for ultrasonic sound emissions as well as a highly developed auditory system for processing species-specific sounds. Because the sounds used by bats for echolocation and rodents for communication are quite different, there must be differences in the central nervous system devoted to producing and processing species-specific sounds between them. The present study examines the difference in the relative size of several brain structures and expression of auditory-related and vocal-related proteins in the central nervous system of echolocation bats and rodents. Here, we report that bats using constant frequency–frequency-modulated sounds (CF–FM bats) and FM bats for echolocation have a larger volume of midbrain nuclei (inferior and superior colliculi) and cerebellum relative to the size of the brain than rodents (mice and rats). However, the former have a smaller volume of the cerebrum and olfactory bulb, but greater expression of otoferlin and forkhead box protein P2 than the latter. Although the size of both midbrain colliculi is comparable in both CF–FM and FM bats, CF–FM bats have a larger cerebrum and greater expression of otoferlin and forkhead box protein P2 than FM bats. These differences in brain structure and protein expression are discussed in relation to their biologically relevant sounds and foraging behavior.